Biological Physics 2000 : Proceedings of the First Workshop Chulalongkorn University, Bangkok, Thailand 18-22 September 2000. - Sa-yakanit, Virulh (World Scientific Publishing Company, 2001)
Like inanimate matter, biological matter is condensed, though it may be more complex. However, a living cell is a chemically open system with biological functions that are often a nonstationary, nonlinear type of collective phenomena driven by chemical reactants, e.g. ATP, GTP, ligands and receptors. The living cell and many of its subsystems are hence lyotropic systems, depending on various reactant concentrations rather than the temperature. Nonlocal and local correlations of the interacting molecules become the prerequisites for signal transduction. This book constitutes the proceedings of.